AI Literacy EFL Classrooms: Preparing Learners for Human–AI Collaboration - Horas Hutabarat (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2026)
The rapid emergence of generative artificial intelligence (AI) has transformed educational practices across disciplines, including English as a Foreign Language (EFL) education. While AI-powered tools offer substantial support for language learning through writing assistance, feedback generation, language practice, and personalized learning experiences, concerns have emerged regarding students’ dependence on AI-generated content, critical evaluation of information, and ethical use of digital technologies. These developments suggest that effective AI integration in language education requires more than technological access and operational skills. This article examines the role of AI literacy in preparing EFL learners for meaningful human–AI collaboration. Employing a qualitative library research design, the study synthesizes recent scholarship on AI literacy, digital literacy, human-centred AI, and AI-assisted language learning. The analysis indicates that AI literacy in EFL contexts encompasses four interconnected dimensions: operational understanding, critical evaluation, ethical awareness, and collaborative competence. Together, these dimensions enable learners to engage with AI systems as reflective users rather than passive consumers of generated content. The study further argues that the educational value of AI depends on learners’ ability to exercise human judgment when interpreting, modifying, and applying AI-generated outputs. Consequently, AI literacy should be integrated into EFL curricula as a foundational competency that supports responsible technology use, critical language learning practices, and sustainable human–AI collaboration in contemporary educational environments.